Restoring hopes through Landscapes: Reviving Nature, water and livelihoods - Singh, Ramesh; Anantha, K.H.; Garg, Kaushal K.; Venkataradha, A.; Shukla, Ashok; Uttam, R.K. (International Crops Research Institute for the Semi-Arid Tropics, 2025)
Across the semi-arid landscapes of Bundelkhand in Central India, water scarcity has long dictated the terms of life, livelihoods, and land use. Yet, within this challenging terrain, the Tahruali cluster in Jhansi district, Uttar Pradesh, offers a transformative story of how science-led, community-driven action can revive degraded landscapes, restore water security, and reimagine the region’s agrarian future. Before the intervention, the Tahruali cluster faced a stark reality. Across 40 villages covering nearly 28,000 hectares, more than 5,400 of the 6,104 wells (both dugwells and borewells) had dried up (Figure 1). Communities depended heavily on erratic monsoons and dwindling groundwater, leaving farms vulnerable and livelihoods uncertain. Recognizing the urgency, ICRISAT and partners, with the support from Government of Uttar Pradesh, initiated a comprehensive landscape resource conservation program that combined traditional wisdom with modern science. The goal was simple yet ambitious: reclaim the landscape for sustainable water futures.